A spatial approach to social media. Issue 6 (19th June 2017) - Laurell, Christofer
Abstract : Purpose: The aim of this paper is to conceptually explore how spatial features of social media can be explained. Design/methodology/approach: Based on a conceptual approach, specific spatial features of social media are reviewed in terms of location, locale and sense of place within the wider frame of the social media landscape. Findings: In the literature stream of social media management and marketing, central conceptualisations relate implicitly to the notions of space and place. By drawing from the field of human geography, this implicit spatiality of social media is made explicit by approaching social media applications as the building blocks of digital space in which digital places are created, maintained and integrated with each other over time as a result of interactions and relationships forming between users that inhabit digital places. Originality/value: The present paper contributes to extant literature by providing a spatial approach to social media that depicts the character of social media, its interrelation with the physical world, as well as how it currently transforms and evolves. Furthermore, it also addresses how social media places represent settings in which social meaning of commercial relevance is created that affects the way consumption activities take place beyond the physical realm of human co-existence.